bahasa inggris: Bahasa Inggris - Basory, Hartomy Akbar; Prastiyo, Yuriko; Wijaya, Satriani (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
ABSTRACT Queuing system management (QSM) can help improve operational efficiency, reduce customer waiting time, a node from human resource management (HRM) based on the effectiveness of HR performance, and optimize employees as HR in improving customer service. This research was conducted with the aim of knowing the mplementing queuing results of system management in one of the Supermarkets in Lampung Province and knowing the optimal number of cashier lines in the QSM. Research conducted on the research object, namely XYZ Supermarket, is recorded every one-hour interval. This research was conducted for 14 days, working hours from 09.00-21.00 Western Indonesian Time zone. The population in this study is all consumers whose population is unlimited. The sample used is consumers who enter the XYZ Supermarket QSM. The study purpose was to optimize the QSM with Ws less than 3 minutes and Ls less than 4 people in accordance with the SOP. This research method uses the multi-channel single-phase model with system time and systems number. The analysis results in this study can be concluded that the performance of the queuing system implemented with the number of cashiers (M) of 2 cashiers at 09.00-09.59, 12.00-12.59, and 19.00-19.59. It makes optimal QSM with Ws less than 3 minutes, and Ls less than 4 people.